Language repertoires of pupils with refugee and migration background: A case study at the 2nd High School of Intercultural Education in Ioannina, Greece - Syrmakesis, Stefanos; Tzouma, Maria; Kousiouri, Evangelia (Glottodidactica, 2024)
This article presents the findings of a case study conducted at the 2nd High School of Intercultural Education in Ioannina, Greece. In the first part, recent statistics on the education of students from refugee and migrant backgrounds are presented, as well as an analysis of concepts such as multilingualism, multilingual and intercultural competence, and multilingual and intercultural education. In the second part, the authors provide an overview of the school’s multilingual development and evaluates key research areas, including the languages spoken by students, their level of proficiency, communication needs, and interventions aimed at fostering the school’s multilingual and intercultural identity. Primary data were collected through questionnaires and the observational research method. The article concludes with recommendations for promoting intercultural awareness and multilingualism as essential elements in school communities. This work is part of the school’s participation in the Erasmus+ project“MaMLiSE: Majority and Minority Languages in School Environment: Helping teachers, pupils, and parents.”